Marine-derived Bioplastics: Sustainable Solutions from the Ocean - Manaswini, C.; Dhanapal, K.; Sravani, K.; Kumar, G. Praveen; Veena, M.; Basha, D. Chand (International Journal of Bio-resource and Stress Management, 2026)
The world’s plastic pollution, resulting from over 500 mmt tons of fossil-fuel-based plastics produced annually, has become a pressing environmental challenge, necessitating sustainable solutions. The continuous increase in plastic production has underscored the urgency of adopting alternatives that are both eco-friendly and efficient. This review focuses on marine-derived biopolymers and bioplastics obtained from renewable resources such as marine algae, fishery by-products, and microorganisms. These materials are not only biodegradable under specific conditions but also exhibit lower carbon footprints and require less energy for production compared to conventional petroleum-based plastics. This review focuses on marine-derived biopolymers and biopolymers obtained from renewable resources such as marine algae, fishery by-products, and microorganisms. These materials are not only biodegradable under specific conditions but also exhibit lower carbon footprints and require less energy for production compared to conventional petroleum-based plastics. By using processes such as extracting chitin and chitosan from crustacean shells, fermenting microbial polymers like polyhydroxyalkanoates (PHA), and utilizing whole algal biomass, these marine-derived bioplastics show how innovation can drive sustainable manufacturing, turn waste into valuable resources, and support responsible stewardship of our oceans, offering hope in the fight against plastic pollution. Overall, this review illustrates how marine-derived bioplastics can drive innovation in sustainable manufacturing, waste valorization, and responsible resource management, offering a comprehensive perspective on their role in mitigating the global plastic pollution crisis.